Ilmu ushulul fiqh - Abdul Wahab Khalaf (Gema Risalah Press, 1996)
ir,c.1-2/ir,c.3/oen, c.4-5/oen, c.6/oen, c.7-8/ir,c.9/oen, c.10/ir,c.11/oen, c.12/ir,c.13/oen, c.14/ir,c.15/ir,c.16/oen, c.17/ast 18-25